Aquatic Toxicology 1980
DOI: 10.1520/stp27425s
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Laboratory-Derived Metal Toxicity Results in Predicting In-Stream Response of Resident Salmonids

Abstract: Acute toxicity and maximum acceptable toxicant concentration (MATC) values, derived under laboratory conditions, provide useful and valid means for predicting environmental impacts of metals on trout populations in natural environments. Toxicity results from in situ bioassays, using unacclimated (hatchery-reared) rainbow trout and other resident salmonids, agree closely with laboratory-derived toxicity findings where fish species, fish size, and water hardness are similar. Concentrations of zinc, copper, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Knowledge of the fate and bioavailability of the materials involved in these studies does not readily explain the differences noted between laboratory toxicity test results and field observations. Furthermore, recent studies present evidence to indicate that natural populations of aquatic organisms have the ability to acclimate to metals such as Zn [1][2][3][4], Cd [1][2][3], Cu [2], and Hg [5], as well as to organic contaminants such as phenol [6] and several pesticides [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the fate and bioavailability of the materials involved in these studies does not readily explain the differences noted between laboratory toxicity test results and field observations. Furthermore, recent studies present evidence to indicate that natural populations of aquatic organisms have the ability to acclimate to metals such as Zn [1][2][3][4], Cd [1][2][3], Cu [2], and Hg [5], as well as to organic contaminants such as phenol [6] and several pesticides [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic responses of several fish species to sublethal chemical concentrations used in the laboratory have changed after prior exposure to sublethal chemical concentrations. Such changes have been recognized for Zn [2,[10][11][12][13][14], Cd [4,[15][16][17], Cu [18][19][20], As [21], Al [22], Cl [23], and synthetic detergents [24]. The majority of these studies were not designed to study changes in acclimation directly; rather, acclimation was reported as a secondary observation, usually in terms of changes in timeto-death of exposed organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the fate and bioavailability of the materials involved in these studies does not readily explain the differences noted between laboratory toxicity test results and field observations. Furthermore, recent studies present evidence to indicate that natural populations of aquatic organisms have the ability to acclimate to metals such as Zn [1–4], Cd [1–3], Cu [2], and Hg [5], as well as to organic contaminants such as phenol [6] and several pesticides [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic responses of several fish species to sublethal chemical concentrations used in the laboratory have changed after prior exposure to sublethal chemical concentrations. Such changes have been recognized for Zn [2,10–14], Cd [4,15–17], Cu [18–20], As [21], Al [22], Cl [23], and synthetic detergents [24]. The majority of these studies were not designed to study changes in acclimation directly; rather, acclimation was reported as a secondary observation, usually in terms of changes in time‐to‐death of exposed organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is commonly found as a contaminant in the Colorado mineral belt and often is associated with waters affected by historic mining activities. Brown trout (Salmo trutta) are an important component of Colorado ecosystems in many headwater streams, but their densities often are reduced because of metal contamination [2]. Limited cadmium toxicity data indicate that brown trout is perhaps the most acutely sensitive aquatic species tested [3].…”
Section: Introductionmentioning
confidence: 99%